“I could not find the strength to resist the pressure of the medical staff, to refuse to give commercial milk formula”: a qualitative study on effects of the war on Ukrainian women’s infant feeding - Iellamo, Alessandro; Wong, Christina Misa; Bilukha, Oleg; Smith, Julie P.; Ververs, Mija; Gribble, Karleen; Walczak, Bartłomiej; Wesolowska, Aleksandra; Al Samman, Sura; O’Brien, Michael; Brown, Annette N.; Stillman, Tobias; et al. (Frontiers in Nutrition, 2024)
During emergencies, breastfeeding protects infants by providing essential nutrients, food security, comfort, and protection and is a priority lifesaving intervention. On February 24, 2022, the war in Ukraine escalated, creating a humanitarian catastrophe. The war has resulted in death, injuries, and mass internal displacement of over 5 million people. A further 8.2 million people have taken refuge in neighboring countries, including Poland. Among those impacted are infants and young children and their mothers. We conducted a study to explore the infant feeding challenges and needs of Ukrainian women affected by the war.We conducted a qualitative descriptive study involving in-depth interviews (IDIs) with 75 waraffected Ukrainian mothers who had at least one infant aged less than 12 months at the time of the interview. Eligible mothers were either 1) living as Ukrainian refugees in Poland, having crossed the border from Ukraine on or after February 24, 2022, when the war started (n=30) or 2) living in Ukraine as internally displaced persons or as residents in the community (n=45). All interviews were audio-recorded (either transcribed or had responses summarized as expanded notes) and analyzed using qualitative thematic analysis using a two-step rapid analysis process.Participants in Ukraine who wanted to initiate breastfeeding right after birth faced opposition from health care workers at maternity hospitals. Ukrainian refugees who gave birth in Poland faced language barriers when seeking breastfeeding support. Half of the participants in Ukraine received commercial milk formula (CMF) donations even if they said they did not need them. Most respondents stated that breastfeeding information and support were urgently needed.Our data suggests that health care workers in Ukrainian maternity hospitals require additional training and motivation on delivering breastfeeding support. In addition, lactation consultants in maternity wards are needed in Ukraine, and interpretation support is needed for refugees to overcome language barriers. There is a need to control the indiscriminate donations of commercial milk formula and to ensure that complementary foods and commercial milk formula are available to those that need it. This study confirms the need for actions to ensure infant and young child feeding (IYCF) support is provided during emergencies.